PROVIDING REGIONAL DEVELOPMENT WITH FOOTBALL INDUSTRY: SİİRT EXAMPLE - AY, Şahin; AKTUĞ, Semih Serkant (Atlas Journal, 2021)
Since football became an industrial sector, production of items related with football raised. Nowadays football marked has created a rise of income and it created common denominator with the other sectors, however it is a reason for other sport related branches to go further in a fundamentally right direction. Study explains; the assessment of the place of “Siirt’s football potential” in the city’s economy, with lead of the connection between industrial football and regional development. The aim of the study is to be an example for; Turkish Football Federation, Youth and Sports Ministry, universities and some governmental offices’ future football plans.